Community Reintegration Problems Among Veterans and Active Duty Service Members With Traumatic Brain Injury. Issue 1 (January 2017) - McGarity, Suzanne; Barnett, Scott D.; Lamberty, Greg; Kretzmer, Tracy; Powell-Cope, Gail; Patel, Nitin; Nakase-Richardson, Risa
Abstract : Objectives: To examine community reintegration problems among Veterans and military service members with mild or moderate/severe traumatic brain injury (TBI) at 1 year postinjury and to identify unique predictors that may contribute to these difficulties. Setting: VA Polytrauma Rehabilitation Centers. Participants: Participants were 154 inpatients enrolled in the VA TBI Model Systems Program with available injury severity data (mild = 28.6%; moderate/severe = 71.4%) and 1-year postinjury outcome data. Design: Prospective, longitudinal cohort. Main Measures: Community reintegration outcomes included independent driving, employability, and general community participation. Additional measures assessed depression, posttraumatic stress, and cognitive and motor functioning. Results: In the mild TBI (mTBI) group, posttraumatic stress disorder and depressive symptoms were associated with lower levels of various community reintegration outcomes. In the moderate/severe TBI group, cognition and motor skills were significantly associated with lower levels of community participation, independent driving, and employability. Conclusion: Community reintegration is problematic for Veterans and active duty service members with a history of TBI. Unique comorbidities across injury severity groups inhibit full reintegration into the community. These findings highlight the ongoing rehabilitation needs of persons with TBI, specifically evidence-based mental healthcare, in comprehensive rehabilitation programs consistent with a chronic disease management model.